A survey on the contributions of power electronics to smart grid systems. (July 2015) - Colak, Ilhami; Kabalci, Ersan; Fulli, Gianluca; Lazarou, Stavros
Abstract: The smart grid (SG) as a research area is advancing dealing with a wider range of topics such as power systems, energy generation and telecommunication. The conventional utility grid is used to operate in a passive mode absorbing energy from the substations and delivering it to the customers. This approach is well developed but the needs of the state-of-the-art technology require a bidirectional flow of power and data. Nevertheless, smart grid systems provide more flexible, reliable, sustainable, secure and two-way communication service. Especially, integration of renewable energy sources, electrical vehicles and distributed generations (DG) into network can be achieved in an efficient way in smart grid systems. Moreover, control and monitoring capabilities, automatic configuration of the grid, and active involvement of consumers in energy production extend the importance of smart grids. All these positive aspects of smart grids have been attained by integration of power electronics and telecommunication technologies with the grid. This study deals with contributions of power electronics to SG in the context of generation, conversion, distribution, and control of power. The recent power electronic devices and systems adapted to SG are also introduced in detail with several power control methods. Moreover, the renewable energy sources (RESs), which are an extensively studied topic of power engineering and their integration to smart grid, are also surveyed in terms of DG units, control and management features. Thus, a particular section is dedicated to RES utilization in SG covering almost all aspects of a monotype and hybrid energy plants. Finally, the survey is carried on by reviewing the most recent and comprehensive articles to highlight the importance of power electronics in a logical way in the smart grids for readers.